2004
DOI: 10.1182/blood-2003-06-1970
|View full text |Cite
|
Sign up to set email alerts
|

Association of biallelic BRCA2/FANCD1 mutations with spontaneous chromosomal instability and solid tumors of childhood

Abstract: The clinical, cytogenetic, and molecular findings of 2 Fanconi anemia (FA) subtype D1 kindreds, initially identified through a young child with a solid tumor (medullobastoma, Wilms tumor), are described. Each kindred subsequently had a second affected child; one developed Wilms tumor followed by a medulloblastoma, and the other developed T-lineage acute lymphoblastic leukemia. Cytogenetic studies revealed an unusually high spontaneous chromosome aberration rate, contrasting with other FA subtypes. Molecular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 32 publications
(48 reference statements)
2
111
0
4
Order By: Relevance
“…12,18 Table 1 gives a review of the 30 patients from 24 families with biallelic BRCA2 mutations and whose phenotype had previously been described in details family. 12,[19][20][21][22][23][24][25][26][27][28] Among these patients, the females and males were equally affected and the mean age of FA diagnosis was 1.9 years (range, 0.1-5.2 years). Most of the patients were diagnosed as FA because of their typical physical features (68%).…”
Section: Discussionmentioning
confidence: 99%
“…12,18 Table 1 gives a review of the 30 patients from 24 families with biallelic BRCA2 mutations and whose phenotype had previously been described in details family. 12,[19][20][21][22][23][24][25][26][27][28] Among these patients, the females and males were equally affected and the mean age of FA diagnosis was 1.9 years (range, 0.1-5.2 years). Most of the patients were diagnosed as FA because of their typical physical features (68%).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the lack of awareness for this rare cancer predisposition syndrome among pediatric hematologists-oncologists, other factors that may play a role in delayed diagnosis include the lack of clearly disease-specific clinical features and the overlap with other cancer predisposing syndromes, including NF1, 1 familial adenomatous polyposis 9 and to some extent also with Fanconi anemia. [40][41][42] In view of the wide tumor spectrum, it has been suggested that CMMR-D should be considered in the differential diagnosis in all pediatric patients with malignancies (except clearly NF1-associated tumors), who show one or more of the following features: (1) CALMs and/or other signs of NF1 and/or hypo-pigmented skin lesions; (2) consanguineous parents; (3) family history of LS-associated tumors; (4) second malignancy; and (5) sibling with childhood cancer. We suggest including ACC with or without gray matter heterotopia as an additional feature.…”
Section: Discussionmentioning
confidence: 99%
“…However, an assessment of the location of BRCA2 mutations in FA-D1 patients in comparison with BRCA2 carriers does not support a bias towards carboxy-terminal mutations in FA-D1 (Reid et al, 2005). Also, the nature of the mutations in many of the reported FA-D1 cases would predict early truncation of the BRCA2 protein expressed from both alleles, and its absence has been confirmed in some cases by Western blot analysis (Hirsch et al, 2004).…”
Section: Cancers In Fa-d1mentioning
confidence: 99%